Transcatheter aortic valve implantation through a transcarotid approach under local anesthesia. Issue 6 (1st February 2014) - Rajagopal, Rajinikanth; More, Ranjit S.; Roberts, David H.
<x xml:space="preserve">Abstract</x> Aims: We report the first experience of transcatheter aortic valve implantation through a transcarotid approach under local anesthesia. Methods and Results: An 81‐year‐old gentleman with severe symptomatic aortic stenosis was referred for TAVI. He was not suitable for transfemoral, transapical, subclavian, or direct aortic approach. He had severe lung disease and was considered unsuitable for general anesthesia. We, therefore, performed the procedure under local anesthesia though the right common carotid artery (CCA) approach. Superficial cervical block was achieved with Levobupivacaine, and in addition, he also had a target controlled infusion of Remifentanil. Cerebral oximetry was monitored throughout the procedure. The CCA was accessed through surgical cut‐down. Aortic valvuloplasty was performed through a 12‐F sheath, and the CoreValve was deployed successfully through an 18‐F sheath. Conclusion: TAVI is commonly performed through femoral access under local anesthesia. The right carotid artery approach under local anesthesia requires careful monitoring of cerebral oxygen levels but allowed us to perform successful TAVI in this high risk patient when all conventional approaches were contra‐indicated. Compared with a right subclavian or left carotid access, the right carotid offers more direct angle of approach allowing precise valve placement with minimal readjustment during deployment. © 2014 Wiley Periodicals, Inc.